Urgensi Revisi Undang-Undang Tentang Wilayah Negara Indonesia - Adinegoro, Ilham Pradana; Setiyono, Joko (JURNAL USM LAW REVIEW, 2023)
This study aims to find out the "gap" and "solution" regarding Indonesian territorial law using a case study of the Sipadan-Ligitan dispute between Indonesia and Malaysia. This later became a lesson for Indonesia to revise the country's territorial law, which is the aim of this research. Using qualitative analysis research methods with literature studies, it was found that until the last law regarding territoriality, namely Law Number 43 of 2008, there was no map image of Indonesia's territory which could be strong evidence of how Indonesia's territory should be, coupled with evidence in In the field there is no strong evidence that Indonesia has managed the two islands in historical records. Thus, the urgency to revise Indonesia's territorial law is needed to prevent similar incidents such as the Sipadan-Ligitan dispute from happening again in the future. Due to the existence of strong legal facts coupled with a strong legal basis regarding territoriality it will be very helpful in resolving territorial disputes such as Sipadan-Ligitan, so that events do not repeat where they lost the argument that led to the International Court of Justice then winning Malaysia based on the principle of effectiveness through evidence of activity administered by Malaysia. Penelitian ini bertujuan untuk mengetahui “celah” dan “solusi” mengenai hukum kewilayahan Indonesia menggunakan studi kasus sengketa Sipadan-Ligitan antara Indonesia dengan Malaysia. Hal ini kemudian menjadi pelajaran berharga bagi Indonesia untuk melakukan revisi undang-undang wilayah negara, yang menjadi tujuan penelitian ini. Menggunakan metode penelitian analisis kualitatif dengan studi literatur, ditemukan bahwa hingga di dalam undang-undang terakhir mengenai kewilayahan yaitu Undang-Undang Nomor 43 Tahun 2008, tidak tercantum gambar peta wilayah Indonesia yang dapat menjadi bukti kuat bagaimana wilayah Indonesia yang seharusnya, ditambah dengan bukti di lapangan tidak terdapat suatu bukti yang kuat bahwa Indonesia telah mengelola kedua pulau tersebut dalam catatan historis. Urgensi untuk merevisi undang-undang wilayah negara Indonesia diperlukan untuk mencegah kejadian serupa seperti sengketa Sipadan-Ligitan terjadi lagi di masa depan. Adanya fakta hukum yang kuat ditambah dengan dasar hukum yang kuat mengenai kewilayahan akan sangat membantu dalam menyelesaikan sengketa wilayah seperti Sipadan-Ligitan, hingga jangan sampai terulang peristiwa dimana kalah dalam argumentasi yang menyebabkan International Court of Justice kemudian memenangkan Malaysia berdasarkan prinsip efektivitas melalui bukti kegiatan administratif yang dilakukan Malaysia.